A mu SR study of high oxidation state iron oxides displaying large magnetoresistance - Marshall, I; Blundell, S; Husmann, A; Jestadt, T; Lovett, B; Pratt, F; Lago, J; Battle, P; Rosseinsky, M (2000)
The magnetic and conducting properties of many transition metal oxides may be drastically altered by doping. This study concerns a family of compounds with compositions intermediate between the itinerant helical antiferromagnet SrFeO3 and the ferromagnetic metal SrCoO3. We have measured the temperature-dependent muon-spin relaxation in five compounds in the family SrFe1-xCoxO3 where Co substitution varies from x = 0 to 0.2 and investigated the relation between the relaxation rate and the magnetic susceptibility above the ordering temperature. These materials show large magnetoresistance which may be associated with the presence of competing interactions and non-equilibrium behaviour due to cluster formation. We find a quasistatic local field at the muon site below the magnetic transition temperature indicative of magnetic order in samples with x = 0.15 and 0.2 but not in the sample with x = 0. (C) 2000 Elsevier Science B.V. All rights reserved.